QUANTITATIVE MEASUREMENT OF BILATERAL CHEILORRHAPHY: A RETROSPECTIVE STUDY - Zarasade, Lobredia; Wulandari, Pratidina; Indri Lakhsmi Putri (Jurnal Rekonstruksi dan Estetik, 2020)
Highlights: There were no significant differences in anthropometric measurements across various groups indicating consistent results in these facial parameters. Bilateral cheilorrhaphy using the Djohansjah technique at the Surabaya CLP Center achieved satisfactory symmetry of the lips, nose, and philtrum, with consistent anthropometric measurements in preoperative cleft conditions. Abstract: Introduction: Bilateral cheilorraphy has higher complexity compared to unilateral cheilorraphy. Anthropometric measurements provide nasolabial identification of the surgery result objectively. This study aims to assess the outcome of bilateral cheilorrhaphy with the Djohansjah technique at Surabaya CLP Center. Methods: 26 patients underwent bilateral cheilorrhaphy from January 1 to December 31, 2018, at the Surabaya CLP Center. Anthropometric measurements were performed on control photos one-year post-surgery with the GIMP application (GNU Image Manipulation Software) version 2.10.12 to measure the cupid's bow width ratio, hemilabial length ratio, nasal width ratio, and philtrum ridge length ratio. A statistical analysis was performed using Independent Sample t-Tes and Mann-Whitney Test. Results: An anthropometric size difference test based on preoperative condition was performed. No significant difference of the cupid's bow width ratio, hemilabial length ratio, nasal width ratio, and philtrum ridge length ratio between the group of identical cleft lip and unidentical cleft lip with p > 0.05 was found. Likewise, there was no difference between the identical cleft alveolar and unidentical cleft alveolar, as well as the group with or without cleft palate. Conclusions: Symmetry of lips, nose, and philtrum was achieved with bilateral cheilorrhaphy with the Djohansjah technique at the Surabaya CLP Center and there was no significant difference in cupid's bow width ratio, hemilabial length ratio, nasal width ratio, and philtrum ridge length ratio on preoperative cleft condition.